Physician's use of laparoscopy. Issue 6147 (4th November 1978) - Barry, R E; Brown, P; Read, A E
Abstract : The role of laparoscopy in medical practice was assessed by studying 238 consecutive laparoscopies performed under local anaesthesia by physicians in a single teaching hospital. Indications for laparoscopy were assessment of possible and known hepatic disease, possible disseminated abdominal malignancy, abdominal mass, and conditions such as ascites and splenomegaly. A definitive diagnosis was reached in 223 cases (76.5%). No organic disease was detected in 41 patients, though findings were false-negative in two of them (0.8%). The procedure failed in 15 (6.3%), mostly because adhesions from previous surgery hindered adequate visualisation. Six patients (2.5%) had complications, one of whom subsequently died. If patients are appropriately selected laparoscopy is relatively free of postoperative complications, and is an effective diagnostic procedure in abdominal malignancy and decompensated liver disease. Cost-effectiveness is an additional advantage.